Discordance Between Stimulated and Spontaneous Growth Hormone Levels in Short Children Is Dependent on Cut-Off Level and Partly Explained by Refractoriness - Lennartsson, Otto; Nilsson, Ola; Lodefalk, Maria (Frontiers in Endocrinology, 2020)
Background: A growth hormone (GH) stimulation test is the recommended method for evaluating GH levels in children with possible GH deficiency (GHD). However, serial measurements of nocturnal spontaneous GH secretion are also performed. Divergent results from these tests have been reported, but with variable frequencies. Objectives: To investigate whether performing one or two GH tests is associated with the probability to diagnose a child with GHD; the frequency of divergent results in the arginine-insulin tolerance test (AITT) and the nocturnal spontaneous test using different cut-off levels, and whether refractoriness may explain some of the discordance. Methods: In a population-based setting, the medical records of all short children evaluated for possible GHD during January 1993–February 2017 were reviewed. Twenty-one patients had been evaluated with one GH test only and 102 children had been evaluated with a spontaneous nocturnal GH test followed immediately by a complete AITT. Divergent results were defined as having a pathological response on only one of the tests when using 3, 5, 7, and 10 µg/L as cut-offs for peak GH on both tests, 1.1 and 3.3 µg/L for mean nocturnal values and receiver operating characteristic curves-derived cut-offs for nocturnal values. Results: Children evaluated with one test only were more often diagnosed with GHD compared with children evaluated with both tests (48% vs. 19%, p = 0.019). Divergent results were found in 6–42% of the patients, with higher frequencies seen when higher cut-offs were applied. A higher proportion of patients with stimulated peak values ≤ 7 and ≤ 5 µg/L had a spontaneous peak within 2 hours before the start of the AITT compared with patients with higher stimulated peak values (68% vs. 45%, p = 0.026, and 77% vs. 48%, p = 0.033, respectively). Conclusions: Divergent results between AITT and nocturnal spontaneous secretion are common in short children, dependent on the cut-offs applied and partly due to refractoriness. Performing both tests decreases the risk of over diagnosing GHD in short children.